2014
DOI: 10.1163/15685411-00002753
|View full text |Cite
|
Sign up to set email alerts
|

Morphological variability in second-stage juveniles and males of Meloidogyne chitwoodi

Abstract: The morphology of Meloidogyne chitwoodi is relatively poorly characterised. In a recent study, morphological variation in adult females of M chitwoodi was analysed. However, comparable data are lacking for adult males and second-stage juveniles (J2). Therefore, our studies of four M. chitwoodi isolates from the western tJSA, representing all currently known races and pathotypes, were designed to characterise intraspecific morphological variability in J2 and males and to compare it to variability found in adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 31 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…These differences we believed to be caused by intraspecies variations are also observed among other populations. In a study, which evaluated the morphological features of male and the second stage larvae belonging to four different American isolate of M. chitwoodi, very high morphological variation was reported (Humphreys-Pereira & Elling, 2014). Karssen (2002) reported that rectum inflated, whereas Golden et al (1980) reported rectum not inflated.…”
Section: Morphological Identificationmentioning
confidence: 99%
“…These differences we believed to be caused by intraspecies variations are also observed among other populations. In a study, which evaluated the morphological features of male and the second stage larvae belonging to four different American isolate of M. chitwoodi, very high morphological variation was reported (Humphreys-Pereira & Elling, 2014). Karssen (2002) reported that rectum inflated, whereas Golden et al (1980) reported rectum not inflated.…”
Section: Morphological Identificationmentioning
confidence: 99%